Magnetic properties of Co implanted TlInS2 and TlGaSe2 crystals - Mikailzade, F.; Sale, A. G.; Kazan, S.; Khaibullin, R. I.; Khalitov, N. I.; Nuzhdin, V. I.; Mammadov, T. G. (Pergamon-Elsevier Science Ltd, 2012)
The results of investigations of magnetic properties of ternary layered TlInS2 and TlGaSe2 ferroelectric crystals implanted with 40 keV Co+ ions at the fluency of 1.0 x 10(17) ion cm(-2) are presented. It has been revealed that high-fluence implantation with Co ions results in metal nanoparticle formation in the near-surface irradiated region. The calculations of Co concentration profiles and SEM studies show that the metal nanoparticles are located under the surface at the depth of about 20 nm, and they originate the irregular-shaped bumps on the surface. The Co-implanted samples exhibited superparamagnetic behaviour at high temperatures and ferromagnetic state at temperatures lower than T-b, where T-b is a blocking temperature of superparamagnetic nanoparticles. It has been suggested that the observed phenomena can be discussed on the basis of strong magnetic dipolar interaction between Co nanoparticles inside the granular composite film formed as a result of implantation. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Magnetic films and multilayers; Nanofabrications